Strengthening the Entrepreneurial Spirit of Malaysian Immigrant Early Childhood through Entrepreneurship Education to Create an Independent Generation in the Future - Sri Hartono; Dwi Warni Wahyuningsih; Yusup Arip (Unram Journal of Community Service, 2025)
Entrepreneurship education from an early age plays a strategic role in shaping children's independent, creative, and innovative character, especially for immigrant children who face social and economic challenges. This study aims to describe the importance of implementing entrepreneurship education for Malaysian immigrant early childhood children as an effort to create an empowered and independent generation in the future. The methods used include participatory, collaborative, and project-based learning approaches that integrate entrepreneurial values into children's daily activities. The results show that implementing entrepreneurship education can foster self-confidence, responsibility, communication skills, and a strong work ethic in children. Additionally, this program also increases parental involvement in the educational process and strengthens solidarity within the immigrant community. Despite persistent challenges such as limited resources, cultural differences, and limited policy support, entrepreneurship education has proven to be an effective instrument for child and community empowerment. Overall, early childhood entrepreneurship education not only prepares young generations for entrepreneurship but also builds the character and independence needed to face future global challenges.